COVID ONLY ON THURSDAYS: DEALING WITH AN INFODEMIC IN LANGUAGE- AND REGION-BASED ONLINE COMMUNITIES - Rohden, Frauke (AoIR Selected Papers of Internet Research, 2023)
Facing the ‘infodemic’ accompanying the coronavirus pandemic, many online communities were faced with questions of how to organize and moderate a deluge of information regarding the virus. On the social media platform Reddit, new communities (subreddits) about the virus quickly emerged. Accompanied by some negotiation and contestation, r/coronavirus eventually became the official platform-wide information channel about the pandemic. However, many existing subreddits nevertheless had to decide how to deal with the topic. Should they ban it from their community and refer to the official subreddit, allow the topic without restrictions, or adapt existing moderation mechanisms to the evolving situation? New localized communities emerged for discussing the course of the pandemic in particular countries or regions. Additionally, communities in languages other than English were facing challenges in dealing with covid-19 content. In this submission, I explore moderation strategies in several region- and language-based subreddits to examine how rules in existing online communities were changed in the light of pandemic information.